Modelling mountain pine beetle-impacted forest wildland fire fuel distributions from remotely piloted aircraft systems imagery and point clouds - Saeid Parsian; Christopher Hopkinson; Craig Coburn; Christopher Watson; Laura Chasmer (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Thermal performance testing of shallow geothermal systems: Insights from field experiments and numerical modelling - Christopher S. Brown; Isa Kolo; Gioia Falcone; Daniel Friedrich; Sean M. Watson (Geothermics, 2026)

A systematic literature inventory on the interaction between dietary factors and environmental chemical exposures for nervous system health outcomes - Chelsea A. Weitekamp; Caleb Watson; Ellen Hata; Kirstin Hester; Urmila P. Kodavanti; Christopher Lau; David M. Lehmann; Colette N. Miller; Rachel M. Shaffer; Fatima Soliman; Martha Powers; Francesca M. Branch (Food and Chemical Toxicology, 2026)

Brightness, colour, polarisation: a multi-instrument observation campaign of the Gorizont-6 satellite - Robert J.S. Airey; Paul Chote; Klaas Wiersema; Ioannis Apergis; James McCormac; James A. Blake; Benjamin F. Cooke; Isobel S. Lockley; Peter J. Wheatley; Daniel Bayliss; Samuel Gill; Christopher A. Watson; et al. (Advances in Space Research, 2026)

N-Acetylcysteine Dose and Treatment Duration in High-Risk Acetaminophen Ingestions Treated Within Eight Hours: A Retrospective Cohort Study - C. James Watson; Michael D. Simpson; Nishita Saraiya; Christopher A. Wilkosz; Michael B. Yu; Michele M. Burns; Mark J. Neavyn; Karen E. Simone; Tania D. Strout (Journal of Medical Toxicology, 2026)
Introduction Toxicologists may use high dose n-acetylcysteine (HD-NAC) for early-treated high-risk acetaminophen ingestions (EHRAI) given concerns over standard NAC (S-NAC) dosing’s efficacy. We utilize the novel, clinically relevant outcome of mean additional 16-hour NAC maintenance infusions (NMI) to evaluate differences in treatment duration for EHRAI patients treated with S-NAC versus HD-NAC. Methods Retrospective multistate poison center study from 1/1/2019-7/4/2024 of patients ≥ 13-years-old who were treated with S-NAC or HD-NAC within eight hours of a high-risk acetaminophen ingestion. The primary outcome was mean additional NMI. Secondary outcomes were NAC infusion duration, hepatotoxicity, coagulopathy, transplant, and death. Sensitivity analyses evaluated for robustness of findings. Results Of 127 included cases, 52.0% (66/127) received HD-NAC. 7.1% (9/127) had anti-peristaltic co-ingestions. HD-NAC cases received more fomepizole (23.1% versus 1.6%; difference 21.1%). Acetaminophen concentrations controlled for time since ingestion were similar (mean acetaminophen ratio for HD-NAC: 2.7, IQR: 2.3, 3.3 versus S-NAC: 2.4, IQR: 2.2, 2.7; difference − 0.3). 26.0% (33/127) received NMI solely for residual detectable serum acetaminophen. There was no difference in mean additional NMI (HD-NAC: 0.53 versus S-NAC: 0.38; p = 0.240). Median NAC infusion durations were equal across groups (21.0; IQR: 21.0, 37.0; difference 0.0) ( p = 0.137). One patient per group developed hepatotoxicity; there were no transplants or deaths. Sensitivity analyses yielded similar results. Conclusions We found no difference in mean NMI for EHRAI based on NAC dose. These findings support additional NMI as an objective, common, clinically relevant outcome for acetaminophen toxicity research.

Unlearned responses of chicks, Gallus gallus domesticus, towards aposematic insect-like stimuli - Christopher H. Taylor; David J.G. Watson; Francis Gilbert; David J. Pritchard; John Skelhorn; Tom Reader (Animal Behaviour, 2026)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

An abrupt change in long-term shoreline behaviour at Roches Beach, Tasmania: An early response to contemporary climate change-induced sea-level rise? - Chris Sharples; Christopher Watson (Marine Geology, 2025)

Bone lead measurements of live condors in field to assess cumulative lead exposure - Aaron J. Specht; Abu Sayed Mohammed Sayam; Chris N. Parish; Timothy J. Hauck; Richard T. Watson; Christopher J. W. McClure; Marc G. Weisskopf (Environmental Science and Pollution Research, 2024)

A sequence of weather‐driven hydrodynamic events stimulates the formation of harmful algal blooms on an oligotrophic lake - Michael R. Kelly; Vincent W. Moriarty; Harry R. Kolar; Guillaume A. R. Auger; Michael E. Henderson; Campbell D. Watson; Rick A. Relyea; Christopher A. Scholz; Charles T. Driscoll; Kevin C. Rose (Limnology and Oceanography, 2024)
Harmful algal blooms (HABs) are common in many eutrophic lakes and frequently associated with nutrient excesses, warm waters, and calm conditions. While HABs can also occur in oligotrophic waterbodies, bloom‐stimulating factors remain elusive for these ecosystems. Here, using a high‐frequency sensor platform supported by hydrodynamic modeling, we document a clearly linked sequence of three hydrodynamic events that immediately preceded each HAB event on Skaneateles Lake, NY during 2018. HABs were first preceded by interactions between internal waves in the thermal structure of the lake with the northern slope of the lakebed. These interactions disturbed sediments resulting in upwelling of nutrient‐rich sediment and possibly cyanobacterial cells into the lower water column. Next, moderate winds stimulated Langmuir circulation which facilitated the transport of material from the lower water column to well‐lit surface waters. Finally, the sequence culminated with a calm wind period, which is often classically associated with surface HAB formation. While individual steps in this sequence occurred independently and repeatedly throughout the year, the complete sequence occurred only eight times, immediately preceding each of the eight documented HABs. We empirically derive thresholds for and timing of the sequence to independently predict HAB occurrence and elevated cyanobacteria levels in the lake. The discovery of this specific and repeated event sequence and the identified thresholds provides the potential for forecasting of HABs days in advance. Ongoing climate change impacts, including increasing water column thermal stratification and changing wind speeds may alter the frequency, timing, and duration of this sequence and consequent HAB formation.

Comparisons of aerosol generation across different musical instruments and loudness - Jianghan Tian; Henry E. Symons; Natalie A. Watson; Justice Archer; Lauren P. McCarthy; Joshua Harrison; Malcolm Kittle; William J. Browne; Brian Saccente-Kennedy; Ruth Epstein; Christopher M. Orton; James D. Calder; et al. (Journal of Aerosol Science, 2024)

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Co-Production of Knowledge at Sumida Farm Trains a New Generation of Community-Engaged Scientists - Jennifer Engels; Barbara Bruno; Emi Suzuki; Kyle Suzuki; Henrietta Dulai; Mackenzie Manning; Donn Viviani; Kekuʻiapōiula Keliipuleole; Brandon Dela Cruz; Kathy Ho; Kyle Kila; Tehani Malterre; et al. (Oceanography, 2024)
The Sumida watercress farm near Pu‘uloa (Pearl Harbor), O‘ahu has been in continuous operation since 1928. This family-run farm (Figure 1a) produces 70% of the state’s watercress crop, making it critical to Hawai‘i’s food production. The farm’s watercress relies completely on water from freshwater springs. However, the amount of water flowing from the springs has declined by half over the last century as a result of groundwater pumping, climate change, and other drivers (Oki, 2005). Mo‘olelo (oral histories) published in Hawaiian language newspapers from 1834 to 1948 document the springs’ use for agriculture and recreation by Hawaiian ali‘i (chiefs) for more than 1,000 years (Engels et al., 2020).

Informal natural greenspaces as places for urban leisure: Perspectives, uses and values from Quebec, Canada - Christopher John Watson; Aurélie Dumont; Julie Fortier; Sylvie Miaux (Urban Forestry & Urban Greening, 2023)

Isopropyl alcohol inhalation versus 5-HT3 antagonists for treatment of nausea: a meta-analysis of randomised controlled trials - James S. Kimber; Joshua G. Kovoor; John M. Glynatsis; Samuel J. West; Thi Thien Nhi Mai; Jonathan Henry W. Jacobsen; Christopher D. Ovenden; Stephen Bacchi; Joseph N. Hewitt; Aashray K. Gupta; Suzanne Edwards; Fiona J. Taverner; et al. (European Journal of Clinical Pharmacology, 2023)
Purpose Nausea is a common and unpleasant sensation for which current therapies such as serotonin (5-HT 3 ) antagonists are often ineffective, while also conferring a risk of potential adverse events. Isopropyl alcohol (IPA) has been proposed as a treatment for nausea. We aimed to compare IPA with 5-HT 3 antagonists for the treatment of nausea across all clinical settings. Methods MEDLINE, EMBASE, PubMed, CENTRAL and CINAHL were searched from inception to 17 July 2023 for randomised controlled trials (RCTs) comparing inhaled IPA and a 5-HT 3 antagonist for treatment of nausea. Severity and duration of nausea, rescue antiemetic use, adverse events and patient satisfaction were the outcomes sought. Risk of bias (RoB) was assessed using Cochrane RoB 2. Random-effects model was used for meta-analysis. Combination of meta-analyses and narrative review was used to synthesise findings. The evidence was appraised using GRADE. Results From 1242 records, 4 RCTs were included with 382 participants. Participants receiving IPA had a significantly lower mean time to 50% reduction in nausea (MD − 20.06; 95% CI − 26.26, − 13.85). Nausea score reduction at 30 min was significantly greater in the IPA group (MD 21.47; 95% CI 15.47, 27.47). IPA led to significantly reduced requirement for rescue antiemetics (OR 0.60; 95% CI 0.37, 0.95; p = 0.03). IPA led to no significant difference in patient satisfaction when compared with a 5-HT 3 antagonist. The overall GRADE assessment of evidence quality ranged from very low to low. Conclusion IPA may provide rapid, effective relief of nausea when compared with 5-HT 3 antagonists.

Sustainability of bioenergy – Mapping the risks & benefits to inform future bioenergy systems - Andrew James Welfle; Alberto Almena; Muhammad Naveed Arshad; Scott William Banks; Isabela Butnar; Katie Jane Chong; SamuelJ.G. Cooper; Helen Daly; Samira Garcia Freites; Fatih Güleç; Christopher Hardacre; Robert Holland; et al. (Biomass and Bioenergy, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Physical and numerical investigation of integral bridge abutment stiffness due to seasonal thermal loading - Sha Luo; Ziyan Huang; Yazan Asia; Flavia De Luca; Raffaele De Risi; John Harkness; Louis Le Pen; Geoff Watson; David Milne; David Chapman; Anastasios Sextos; Nicole Metje; et al. (Transportation Geotechnics, 2023)

An improved method for computing tidal datums - Karen Palmer; Christopher S. Watson; John R. Hunter; Ben S. Hague; Hannah E. Power (Coastal Engineering, 2023)

Comparison of state-of-the-art GNSS-observed and predicted ocean tide loading displacements across Australia - Bogdan Matviichuk; Matt King; Christopher Watson; Machiel Bos (Journal of Geodesy, 2023)
We seek to quantify and understand the residual signal in GPS and GLONASS estimates of ocean tide loading displacements (OTLDs) after removing state-of-the-art model estimates. To consider contributions over a broad spatial scale, we estimate OTLD over the Australian continent using $$\sim $$ ∼ 5.5 years of continuous GPS and GLONASS data from 360 sites. We compare these with modelled estimates, with a focus on the lunar semidiurnal M $$_2$$ 2 and diurnal O $$_1$$ 1 constituents. We observe spatially coherent patterns of residual OTLD in each of the east, north, and up coordinate components after the removal of tidal loading using elastic models. We subsequently assess the impact of including anelastic dispersion in the model and show a 0.2 mm reduction in range of the up component residuals at coastal sites. A similar reduction at all sites is observed in the east and north components. Of the seven ocean tide models used, we find that three recent models, FES2014b, GOT4.10c and TPXO9.v1, perform similarly, noting these comparisons are made in the CE frame. However, we show that the latter contains centre of mass (CoM) biases in amplitude up to 0.2 mm and 0.5 mm for M $$_2$$ 2 and O $$_1$$ 1 , respectively, due to the assimilated altimetry data having not been corrected for geocentre motion. We find OTLD estimates are sensitive to the chosen orbit and clock products used in our analysis, with differences of up to 0.5 mm in the east component between solutions using the JPL and either of ESA or CODE products (GPS-only). Our analysis shows that current GNSS estimates of OTLD over Australia are typically accurate to $$\sim $$ ∼ 0.2 mm at which point we are unable to explain spatially coherent residuals when compared to modelled quantities. These may depend on the appropriate treatment of the CoM variation, anelasticity and/or three-dimensional Earth structure. As such, we recommend great care is taken when interpreting OTLD at the level of 0.1 or 0.2 mm, even if it is regionally coherent.

Deconstructing heterogeneity of replicative senescence in human mesenchymal stem cells at single cell resolution - Atefeh Taherian Fard; Hannah C. Leeson; Julio Aguado; Giovanni Pietrogrande; Dominique Power; Cecilia Gómez-Inclán; Huiwen Zheng; Christopher B. Nelson; Farhad Soheilmoghaddam; Nick Glass; Malindrie Dharmaratne; Ebony R. Watson; et al. (GeroScience, 2023)
Following prolonged cell division, mesenchymal stem cells enter replicative senescence, a state of permanent cell cycle arrest that constrains the use of this cell type in regenerative medicine applications and that in vivo substantially contributes to organismal ageing. Multiple cellular processes such as telomere dysfunction, DNA damage and oncogene activation are implicated in promoting replicative senescence, but whether mesenchymal stem cells enter different pre-senescent and senescent states has remained unclear. To address this knowledge gap, we subjected serially passaged human ESC-derived mesenchymal stem cells (esMSCs) to single cell profiling and single cell RNA-sequencing during their progressive entry into replicative senescence. We found that esMSC transitioned through newly identified pre-senescent cell states before entering into three different senescent cell states. By deconstructing this heterogeneity and temporally ordering these pre-senescent and senescent esMSC subpopulations into developmental trajectories, we identified markers and predicted drivers of these cell states. Regulatory networks that capture connections between genes at each timepoint demonstrated a loss of connectivity, and specific genes altered their gene expression distributions as cells entered senescence. Collectively, this data reconciles previous observations that identified different senescence programs within an individual cell type and should enable the design of novel senotherapeutic regimes that can overcome in vitro MSC expansion constraints or that can perhaps slow organismal ageing.

Small island nations can achieve food security benefits through climate-adaptive blue food governance by 2050 - Lida Teneva; Christopher M. Free; Andrew Hume; Vera N. Agostini; Carissa J. Klein; Reg A. Watson; Steven D. Gaines (Marine Policy, 2023)

Characteristics of fine and ultrafine aerosols in the London underground - Prashant Kumar; Juan C. Zavala-Reyes; Gopinath Kalaiarasan; Hisham Abubakar-Waziri; Gloria Young; Ian Mudway; Claire Dilliway; Ramzi Lakhdar; Sharon Mumby; Michał M. Kłosowski; Christopher C. Pain; Ian M. Adcock; et al. (Science of The Total Environment, 2023)

Development of a GNSS/INS buoy array in preparation for SWOT validation in Bass Strait - Boye Zhou; Christopher Watson; Jack Beardsley; Benoit Legresy; Matt A. King (Frontiers in Marine Science, 2023)
In preparation for validation of the swath-based altimetry mission (Surface Water Oceanography Topography, SWOT), we developed a buoy array, equipped with Global Navigation Satellite System/Inertial Navigation System, capable of accurately observing sea surface height (SSH), wave information and tropospheric delay. Here we present results from an 8-day trial deployment at five locations along a Sentinel-6 Michael Freilich (S6MF) ground track in Bass Strait. A triplet buoy group including two new buoys (Mk-VI) and a single predecessor (Mk-IV) were deployed in proximity to the historic Jason-series comparison point. SSH solutions compared against an in-situ mooring suggest the new buoys were working at an equivalent precision of ~1.5 cm to the previous design (MK-IV). At 10-km spacing along the S6MF track, the buoy array was shown to observe the progression of oceanographic and meteorological phenomena. Tidal analysis of the buoy array indicated moderate spatial variability in the shallow water tidal constituents, with differences in the instantaneous tidal height of up to ~0.2 m across the 40-km track. Further, tidal resonance within Bass Strait was observed to vary, most probably modulated by atmospheric conditions, yet only partially captured by an existing dynamic atmospheric correction product. A preliminary investigation into the spatial scale of the buoy error based on observed/inferred geostrophic currents with our present buoy array configuration suggests that the signal-noise ratio of the array became significant at 20-km spacing in Bass Strait. Finally, as an illustrative comparison between the buoy array and high resolution S6MF data, a single cycle was compared. The wet tropospheric delay observed by the S6MF radiometer exhibited some potential land contamination in the deployed area, while the 1-Hz and 20-Hz significant wave height from S6MF appeared within mission requirements. Generally good agreement between buoy and altimeter SSH was observed. However, subtle differences between the altimeter and the buoy sea level anomaly series warrants further investigation with additional cycles from a sustained deployment in the area. We conclude that the buoy array offers a useful geodetic tool to help quantify and understand intra-swath variability in the context of the SWOT mission.

Vertical deformation and residual altimeter systematic errors around continental Australia inferred from a Kalman-based approach - Mohammad-Hadi Rezvani; Christopher S. Watson; Matt A. King (Journal of Geodesy, 2022)
We further developed a space–time Kalman approach to investigate time-fixed and time-variable signals in vertical land motion (VLM) and residual altimeter systematic errors around the Australian coast, through combining multi-mission absolute sea-level (ASL), relative sea-level from tide gauges (TGs) and Global Positioning System (GPS) height time series. Our results confirmed coastal subsidence in broad agreement with GPS velocities and unexplained by glacial isostatic adjustment alone. VLM determined at individual TGs differs from spatially interpolated GPS velocities by up to ~ 1.5 mm/year, yielding a ~ 40% reduction in RMSE of geographic ASL variability at TGs around Australia. Our mission-specific altimeter error estimates are small but significant (typically within ~ ± 0.5–1.0 mm/year), with negligible effect on the average ASL rate. Our circum-Australia ASL rate is higher than previous results, suggesting an acceleration in the ~ 27-year time series. Analysis of the time-variability of altimeter errors confirmed stability for most missions except for Jason-2 with an anomaly reaching ~ 2.8 mm/year in the first ~ 3.5 years of operation, supported by analysis from the Bass Strait altimeter validation facility. Data predominantly from the reference missions and located well off narrow shelf regions was shown to bias results by as much as ~ 0.5 mm/year and highlights that residual oceanographic signals remain a fundamental limitation. Incorporating non-reference-mission measurements well on the shelf helped to mitigate this effect. Comparing stacked nonlinear VLM estimates and altimeter systematic errors with the El Niño-Southern Oscillation shows weak correlation and suggests our approach improves the ability to explore nonlinear localized signals and is suitable for other regional- and global-scale studies.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

TitaniQ revisited: expanded and improved Ti-in-quartz solubility model for thermobarometry - Zach R. Osborne; Jay B. Thomas; William O. Nachlas; Ross J. Angel; Christopher M. Hoff; E. Bruce Watson (Contributions to Mineralogy and Petrology, 2022)

Aluminum solubility in rutile (TiO2) - Christopher M. Hoff; E. Bruce Watson (Physics and Chemistry of Minerals, 2021)

The importance of Indigenous Peoples’ lands for the conservation of terrestrial mammals - Christopher J. O'Bryan; Stephen T. Garnett; Julia E. Fa; Ian Leiper; Jose A. Rehbein; Álvaro Fernández‐Llamazares; Micha V. Jackson; Harry D. Jonas; Eduardo S. Brondizio; Neil D. Burgess; Catherine J. Robinson; Kerstin K. Zander; et al. (Conservation Biology, 2021)
Indigenous Peoples’ lands cover over one‐quarter of Earth's surface, a significant proportion of which is still free from industrial‐level human impacts. As a result, Indigenous Peoples and their lands are crucial for the long‐term persistence of Earth's biodiversity and ecosystem services. Yet, information on species composition on these lands globally remains largely unknown. We conducted the first comprehensive analysis of terrestrial mammal composition across mapped Indigenous lands based on data on area of habitat (AOH) for 4460 mammal species assessed by the International Union for Conservation of Nature. We overlaid each species’ AOH on a current map of Indigenous lands and found that 2695 species (60% of assessed mammals) had ≥10% of their ranges on Indigenous Peoples’ lands and 1009 species (23%) had >50% of their ranges on these lands. For threatened species, 473 (47%) occurred on Indigenous lands with 26% having >50% of their habitat on these lands. We also found that 935 mammal species (131 categorized as threatened) had ≥ 10% of their range on Indigenous Peoples’ lands that had low human pressure. Our results show how important Indigenous Peoples’ lands are to the successful implementation of conservation and sustainable development agendas worldwide.

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The impact of oral rehabilitation coupled with healthy dietary advice on the nutritional status of adults: A systematic review and meta-analysis - Laura McGowan; Leigh-Ann McCrum; Sinead Watson; Christopher Cardwell; Bernadette McGuinness; Helen Rutherford; Victoria Paice; Ciaran Moore; Paul R. Brocklehurst; Jayne V. Woodside; Gerald McKenna (Critical Reviews in Food Science and Nutrition, 2020)

Opportunities for agent‐based modelling in human dimensions of fisheries - Matthew G. Burgess; Ernesto Carrella; Michael Drexler; Robert L. Axtell; Richard M. Bailey; James R. Watson; Reniel B. Cabral; Michaela Clemence; Christopher Costello; Chris Dorsett; Steven D. Gaines; Emily S. Klein; et al. (Fish and Fisheries, 2020)
Models of human dimensions of fisheries are important to understanding and predicting how fishing industries respond to changes in marine ecosystems and management institutions. Advances in computation have made it possible to construct agent‐based models (ABMs)—which explicitly describe the behaviour of individual people, firms or vessels in order to understand and predict their aggregate behaviours. ABMs are widely used for both academic and applied purposes in many settings including finance, urban planning and the military, but are not yet mainstream in fisheries science and management, despite a growing literature. ABMs are well suited to understanding emergent consequences of fisher interactions, heterogeneity and bounded rationality, especially in complex ecological, social and institutional contexts. For these reasons, we argue that ABMs of human behaviour can contribute significantly to human dimensions of fisheries in three areas: (a) understanding interactions between multiple management institutions; (b) incorporating cognitive and behavioural sciences into fisheries science and practice; and (c) understanding and projecting the social consequences of management institutions. We provide simple examples illustrating the potential for ABMs in each of these areas, using conceptual (“toy”) versions of the POSEIDON model. We argue that salient strategic advances in these areas could pave the way for increased tactical use of ABMs in fishery management settings. We review common ABM development and application challenges, with the aim of providing guidance to beginning ABM developers and users studying human dimensions of fisheries.

Economic Impact of Globodera Pallida on the Idaho Economy - Samjhana Koirala; Philip Watson; Christopher S. McIntosh; Louise-Marie Dandurand (American Journal of Potato Research, 2020)

The mesoscavenger release hypothesis and implications for ecosystem and human well‐being - Christopher J. O'Bryan; Matthew H. Holden; James E.M. Watson (Ecology Letters, 2019)
Many apex scavenger species, including nearly all obligate scavengers, are in a state of rapid decline and there is growing evidence these declines can drastically alter ecological food webs. Our understanding of how apex scavengers regulate populations of mesoscavengers, those less‐efficient scavengers occupying mid‐trophic levels, is improving; yet, there has been no comprehensive evaluation of the evidence around the competitive release of these species by the loss of apex scavengers. Here we present current evidence that supports the mesoscavenger release hypothesis, the increase in mesoscavengers and increase in carrion in the face of declining apex scavengers. We provide two models of scavenger dynamics to demonstrate that the mesoscavenger release hypothesis is consistent with ecological theory. We further examine the ecological and human well‐being implications of apex scavenger decline, including carrion removal and disease regulation services.

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

How ecology shapes exploitation: a framework to predict the behavioural response of human and animal foragers along exploration–exploitation trade‐offs - Christopher T. Monk; Matthieu Barbier; Pawel Romanczuk; James R. Watson; Josep Alós; Shinnosuke Nakayama; Daniel I. Rubenstein; Simon A. Levin; Robert Arlinghaus (Ecology Letters, 2018)
Understanding how humans and other animals behave in response to changes in their environments is vital for predicting population dynamics and the trajectory of coupled social‐ecological systems. Here, we present a novel framework for identifying emergent social behaviours in foragers (including humans engaged in fishing or hunting) in predator–prey contexts based on the exploration difficulty and exploitation potential of a renewable natural resource. A qualitative framework is introduced that predicts when foragers should behave territorially, search collectively, act independently or switch among these states. To validate it, we derived quantitative predictions from two models of different structure: a generic mathematical model, and a lattice‐based evolutionary model emphasising exploitation and exclusion costs. These models independently identified that the exploration difficulty and exploitation potential of the natural resource controls the social behaviour of resource exploiters. Our theoretical predictions were finally compared to a diverse set of empirical cases focusing on fisheries and aquatic organisms across a range of taxa, substantiating the framework's predictions. Understanding social behaviour for given social‐ecological characteristics has important implications, particularly for the design of governance structures and regulations to move exploited systems, such as fisheries, towards sustainability. Our framework provides concrete steps in this direction.

Analysis of nonlinear associations between prenatal methylmercury exposure from fish consumption and neurodevelopmental outcomes in the Seychelles Main Cohort at 17 years - Li-Shan Huang; Deborah A. Cory-Slechta; Christopher Cox; Sally W. Thurston; Conrad F. Shamlaye; Gene E. Watson; Edwin van Wijngaarden; Grazyna Zareba; J. J. Strain; Gary J. Myers; Philip W. Davidson (Stochastic Environmental Research and Risk Assessment, 2018)

Trade‐offs in triple‐bottom‐line outcomes when recovering fisheries - Christopher J Brown; Glenn Althor; Benjamin S Halpern; Md Sayed Iftekhar; Carissa J Klein; Simon Linke; Elizabeth C Pryde; Steven Schilizzi; James E M Watson; Becky Twohey; Hugh P Possingham (Fish and Fisheries, 2018)
Almost all environmental management comes at an economic cost that may not be borne equitably by all stakeholders. Here, we investigate how heterogeneity in catch and profits among fishers influences the trade‐off among the triple‐bottom‐line objectives of recovering a fish population, maximizing its economic value and distributing restrictions equitably across fishers. As a case‐study, we examine management reform of an ecologically and economically important coral reef fishery operating within the Great Barrier Reef Marine Park. Using a simulation model, we find that total profitability of the fishing industry is 40% lower if recovery plans are equitable when compared to the most economically efficient plan. However, efficient recovery plans were typically highly inequitable because they required some fishers to cease fishing. Equity was defined according to different norms, and the efficiency loss was greatest when catch losses were shared equally across fishers rather than in proportion to their historical catch. We then varied key social, economic and biological parameters to identify cases when equity and efficient recovery would trade‐off most strongly. Recovery plans could be both efficient and equitable when heterogeneity in fisher's catches and individual catch efficiencies was lower. If fishers were homogenous then equitable plans could have maximal economic efficiency. These results emphasize the importance of considering heterogeneity in individual fishers when designing recovery plans. Recovery plans that are inequitable may often fail to gain stakeholder support, so in fisheries with high heterogeneity we should temper our expectations for marked increases in profits.

White matter hyperintensities correlate to cognition and fiber tract integrity in older adults with HIV - Christa Watson; Edgar Busovaca; Jessica M. Foley; I. Elaine Allen; Christopher G. Schwarz; Neda Jahanshad; Talia M. Nir; Pardis Esmaeili-Firidouni; Benedetta Milanini; Howard Rosen; Owen T. Carmichael; Paul M. Thompson; et al. (Journal of NeuroVirology, 2017)

Local tidal regime dictates plasticity of expression of locomotor activity rhythms of American horseshoe crabs, Limulus polyphemus - Rebecca L. Anderson; Winsor H. Watson; Christopher C. Chabot (Marine Biology, 2017)

Remote leveling of tide gauges using GNSS reflectometry: case study at Spring Bay, Australia - Alvaro Santamaría-Gómez; Christopher Watson (GPS Solutions, 2017)

Epigenetic variation among natural populations of the South African sandhopper Talorchestia capensis - Simone Baldanzi; Ralph Watson; Christopher D. McQuaid; Gavin Gouws; Francesca Porri (Evolutionary Ecology, 2017)

Understanding social–ecological vulnerability with Q-methodology: a case study of water-based ecosystem services in Wyoming, USA - Christopher Armatas; Tyron Venn; Alan Watson (Sustainability Science, 2017)

Influence of Environmental Factors on Spawning of the American Horseshoe Crab (Limulus polyphemus) in the Great Bay Estuary, New Hampshire, USA - Helen Cheng; Christopher C. Chabot; Winsor H. Watson (Estuaries and Coasts, 2016)

Comparing the effects of calibration and climate errors on a statistical crop model and a process-based crop model - James Watson; Andrew J. Challinor; Thomas E. Fricker; Christopher A. T. Ferro (Climatic Change, 2015)

Levelling co-located GNSS and tide gauge stations using GNSS reflectometry - Alvaro Santamaría-Gómez; Christopher Watson; Médéric Gravelle; Matt King; Guy Wöppelmann (Journal of Geodesy, 2015)

Empirical modelling of site-specific errors in continuous GPS data - Michael Moore; Christopher Watson; Matt King; Simon McClusky; Paul Tregoning (Journal of Geodesy, 2014)

The effects of frequency-dependent quasar variability on the celestial reference frame - Stanislav S. Shabala; Jonathan G. Rogers; Jamie N. McCallum; Oleg A. Titov; Jay Blanchard; James E. J. Lovell; Christopher S. Watson (Journal of Geodesy, 2014)

Continental‐Scale Governance and the Hastening of Loss of Australia's Biodiversity - Euan G. Ritchie; Corey J. A. Bradshaw; Chris R. Dickman; Richard Hobbs; Christopher N. Johnson; Emma L. Johnston; William F. Laurance; David Lindenmayer; Michael A. McCarthy; Dale G. Nimmo; Hugh H. Possingham; Robert L. Pressey; et al. (Conservation Biology, 2013)

Combined walking exercise and alkali therapy in patients with CKD4–5 regulates intramuscular free amino acid pools and ubiquitin E3 ligase expression - Emma L. Watson; George C. Kosmadakis; Alice C. Smith; Joao L. Viana; Jeremy R. Brown; Karen Molyneux; Izabella Z. A. Pawluczyk; Michael Mulheran; Nicolette C. Bishop; Susan Shirreffs; Ronald J. Maughan; Paul J. Owen; et al. (European Journal of Applied Physiology, 2013)

Impacts of inundation and drought on eukaryote biodiversity in semi‐arid floodplain soils - Darren S. Baldwin; Matthew J. Colloff; Gavin N. Rees; Anthony A. Chariton; Garth O. Watson; Leon N. Court; Diana M. Hartley; Matthew j. Morgan; Andrew J. King; Jessica S. Wilson; Michael Hodda; Christopher M. Hardy (Molecular Ecology, 2013)
Floodplain ecosystems are characterized by alternating wet and dry phases and periodic inundation defines their ecological character. Climate change, river regulation and the construction of levees have substantially altered natural flooding and drying regimes worldwide with uncertain effects on key biotic groups. In southern A ustralia, we hypothesized that soil eukaryotic communities in climate change affected areas of a semi‐arid floodplain would transition towards comprising mainly dry‐soil specialist species with increasing drought severity. Here, we used 18S r RNA amplicon pyrosequencing to measure the eukaryote community composition in soils that had been depleted of water to varying degrees to confirm that reproducible transitional changes occur in eukaryotic biodiversity on this floodplain. Interflood community structures (3 years post‐flood) were dominated by persistent rather than either aquatic or dry‐specialist organisms. Only 2% of taxa were unique to dry locations by 8 years post‐flood, and 10% were restricted to wet locations (inundated a year to 2 weeks post‐flood). Almost half (48%) of the total soil biota were detected in both these environments. The discovery of a large suite of organisms able to survive nearly a decade of drought, and up to a year submerged supports the concept of inherent resilience of Australian semi‐arid floodplain soil communities under increasing pressure from climatic induced changes in water availability.

Observations of below-ground characteristics of young redwood trees (Sequoia sempervirens) from two sites in New Zealand – implications for erosion control - Christopher J. Phillips; Michael Marden; Suzanne Lambie; Alex Watson; Craig Ross; Scott Fraser (Plant and Soil, 2013)

Cross-linking of structural proteins in ageing skin: an in situ assay for the detection of amine oxidase activity - Abigail K. Langton; Christopher E. M. Griffiths; Michael J. Sherratt; Rachel E. B. Watson (Biogerontology, 2013)

Differential expression of elastic fibre components in intrinsically aged skin - Abigail K. Langton; Michael J. Sherratt; Christopher E. M. Griffiths; Rachel E. B. Watson (Biogerontology, 2012)

Absolute Calibration in Bass Strait, Australia: TOPEX, Jason-1 and OSTM/Jason-2 - Christopher Watson; Neil White; John Church; Reed Burgette; Paul Tregoning; Richard Coleman (Marine Geodesy, 2011)

Use of a serum‐based glomerular filtration rate prediction equation to assess renal function by age, sex, fasting, and health status in bottlenose dolphins ( Tursiops truncatus ) - Stephanie Venn‐Watson; Cynthia R. Smith; Christopher Dold; Sam H. Ridgway (Marine Mammal Science, 2008)
Glomerular filtration rate (GFR) is a direct measurement of renal function. Although clearance tests using 24‐h urine collection or blood sample series are gold standards for measuring GFR, serum‐based prediction of GFR based upon the Modification of Diet in Renal Disease (MDRD) Study equation is acceptable for routine use in human adults. The purpose of our study was to assess the ability for a modified MDRD Study equation to predict expected changes in GFR in bottlenose dolphins ( Tursiops truncatus ) using a healthy dolphin population represented by 1,103 routine serum samples collected from 50 dolphins of all age groups, years 1998–2005. Predicted GFR was also calculated from serum collected from a 32‐yr‐old male dolphin with end‐stage renal disease. The dolphin‐adjusted MDRD equation predicted GFR changes in our population that paralleled what has previously been reported in other mammals, including decreasing predicted GFR with age ( P P

MTHFR (C677T and A1298C) Polymorphisms and Risk of Sporadic Distal Colorectal Adenoma in the UK Flexible Sigmoidoscopy Screening Trial (United Kingdom) - Panagiota N. Mitrou; Mark A. Watson; Alexandre S. Loktionov; Christopher Cardwell; Marc J. Gunter; Wendy S. Atkin; Christopher P. Macklin; Tom Cecil; Timothy D. Bishop; John Primrose; Sheila A. Bingham (Cancer Causes & Control, 2006)

Morphogenesis in Sitka spruce (Picea sitchensis (Bong.) Carr.) bud cultures – tree maturation and explants from epicormic shoots - Christopher Selby; Sally Watson; Barbara M. R. Harvey (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Intracranial injections induce local transcription of a gene encoding precerebellin-like protein - Lena Gerwick; Graham E. Corley-Smith; Miki Nakao; Jeff Watson; Christopher J. Bayne (Fish Physiology and Biochemistry, 2005)

Narcissus bulblet formation in vitro: effects of carbohydrate type and osmolarity of the culture medium - Ioanna Staikidou; Sally Watson; Barbara M. R. Harvey; Christopher Selby (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Natural product extracts that reduce accumulation of the alzheimer’s amyloid β peptide - Debra Yager; Mona Watson; Brent Healy; Elizabeth A. Eckman; Christopher B. Eckman (Journal of Molecular Neuroscience, 2002)

An examination of the sensitivity of reported trends in childhood leukemia incidence rates to geographic location and diagnostic coding (United States) - Gary L. Liberson; Robert J. Golden; William J. Blot; Harry Fisch; Christopher Watson (Cancer Causes & Control, 2000)